2021
DOI: 10.3390/jpm11060468
|View full text |Cite
|
Sign up to set email alerts
|

Association of LINC00673 Genetic Variants with Progression of Oral Cancer

Abstract: Oral squamous cell carcinoma (OSCC) is a multifactorial malignancy, and its high incidence and mortality rate remain a global public health burden. Polymorphisms in the long intergenic noncoding RNA 673 (LINC00673) have been currently connected to the predisposition to various cancer types. The present study attempted to explore the impact of LINC00673 gene polymorphisms on the risk and progression of OSCC. Three LINC00673 single-nucleotide polymorphisms (SNPs), including rs11655237, rs9914618, and rs6501551, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 43 publications
(66 reference statements)
1
26
0
Order By: Relevance
“…A total of three LINC00673 SNPs, namely, rs6501551 (A/G), rs9914618 (G/A), and rs11655237 (C/T), were selected for phenotype analyses because the minor allele frequencies of these SNPs were higher than 5% and our preceding research indicated the effect of these SNPs on other cancers ( Su et al, 2021a ). The procedures for DNA extraction and phenotype analyses in this study were in accordance with those of our previous study ( Su S. C. et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of three LINC00673 SNPs, namely, rs6501551 (A/G), rs9914618 (G/A), and rs11655237 (C/T), were selected for phenotype analyses because the minor allele frequencies of these SNPs were higher than 5% and our preceding research indicated the effect of these SNPs on other cancers ( Su et al, 2021a ). The procedures for DNA extraction and phenotype analyses in this study were in accordance with those of our previous study ( Su S. C. et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Among this group, long intergenic noncoding RNA 00673 (LINC00673) is associated with several malignancies ( Zhu K. et al, 2021 ; Zhu Y. et al, 2021 ). In addition, LINC00673 SNPs can influence the expression of cancers such as oral cancer and gastric cancer ( Zhao et al, 2019 ; Su et al, 2021a ). Nevertheless, research on the relationship between the SNPs of LINC00673 and DR development is rare.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, sexually transmitted diseases, such as HPV-mediated (p16) [ 8 ], are also associated with oral cancer. However, genome-wide and targeted-gene association studies [ 9 , 10 ] have found relationships between single-nucleotide polymorphisms and carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue, Functional Genomics and Pharmacogenomics in Human Disease, covers 15 publications conducted by various groups, including nine original research papers, five review papers, and one case report. Original research papers consist of genetic discovery and functional characterization of CYP1A2 and CYP2C9 [ 1 , 2 ], genetic studies of oral cancer [ 3 , 4 , 5 ], chronic obstruction pulmonary disease (COPD) [ 6 ], asthma [ 7 ], diabetic kidney disease [ 8 ], and web-based pharmacogenomics tool development [ 9 ]. Review papers include the thiopurine treatments with NUDT15 polymorphisms [ 10 ], lipid lowering therapies in familial hypercholesterolemia [ 11 ], incorporation of genetic addiction risk severity (GARS) to overcome the addiction pandemic [ 12 ], and the latest update on genetic variants of UGT [ 13 ] and SULT genes [ 14 ].…”
mentioning
confidence: 99%
“…Oral cancer research was conducted with genetics and presented the risk of cancer occurrence, the sensitivity of cancer development, and the degree of cancer progression related to genetic variants. MACC1 [ 3 ], LINC00673 [ 4 ], and IncRNA GASS5 [ 5 ] were investigated, and the correlation between the mutants of these genes and oral cancer was described. If additional genetic variants related to oral cancer are further studied on the present patients, it is expected to provide important information that is very practical for personalized treatment and prevention of oral cancer.…”
mentioning
confidence: 99%